CHANGES IN CHINA-UZBEKISTAN RELATIONS DURING THE FIRST ADMINISTRATION OF SH.MIRZIYOYEV THROUGH THE LENSES OF REALISM WITH COMPARISON OF OTHER NEW INTERNATIONAL RELATIONS THEORIES. - Kholboeva Zarifa Odil kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: It is clear by the history that China and Uzbekistan had close relations thanks to the Silk Road which linked these countries even at that time with economic relations. While having bilateral relations, from the history , Sun Szu 1 , in his book , The art of war,  wrote a lot about Chinese type of thinking of realistic point-views. Furthermore, the recent initiatives and strategies of both countries shows the elements of realism when both of the countries are of paramount importance in terms of regional and global geopolitical scheme as one of them is located in Central Asia and the other one is in the Far East which is strategically, economically and politically vital when it comes to policy of the country. However, China has not only been trying to survive but also  to expand and gain power over  other countries with its soft power techniques. This paper will elaborate the factors that are responsible for the  behavior of these countries and the role of national interests and power dynamics.